LANDSCAPE AND GEOCHEMICAL FEATURES OF THE TERRITORY OF THE CITY OF VYZHNYTSIA, CHERNIVTSI OBLAST - KHODAN, Halyna (My University, 2022)
A significant differentiation of landscape areas and tracts of the territory determines the diversity of its natural geochemical landscapes, which is enhanced by the anthropogenic and man-made load. The latter enhances the geochemical differentiation of geochemical parameters, mainly in places of man-made contact.
Keywords: landscape, geochemical zoning, settlement landscape, natural landscape.